HEADLINE INFLATION AND CONSUMERS' CONFIDENCE IN NIGERIA - Aberu, Felix (Jurnal Ekonomi dan Bisnis Airlangga, 2023)
Introduction: The Nigerian economy experienced a significant growth turning point in early 2000 after returning to democratic rule in 1999. Nonetheless, the country's strong economic growth has done little to address the issues such as poverty, inequality, unemployment, the exchange rate, inflation, and interest rate spread. As a result, consumer confidence falls, resulting in lower spending. Methods: The ARDL model was used to highlight the importance of consumer confidence (household spending) and inflation in Nigeria using data from the cbn survey of consumer expectations from 1996 to 2022. Results: The findings show that a unit increase in headline inflation corresponds to a 0.01 increase in consumer confidence, implying that consumers lose 99.99 percent of their confidence at every point of increase in headline inflation, indicating that headline inflation is a core determinant of consumption in Nigeria. Conclusion and suggestion: In light of the study's findings, the federal government should consider raising the nation's minimum wage, among other policy options, in order to increase household consumption expenditures. Furthermore, Nigerian government policies should address disparities in consumption among the citizenries.